Impact of match-related contextual variables on weekly training load in a professional soccer team: a full season study - M. Oliva Lozano, Jose; Rago, Vincenzo; Fortes, Víctor; M. Muyor, José (Biology of Sport, 2022)
The purpose of this study was to analyse the impact of match-related contextual variables (match location, match outcome and level of the opponent) on the weekly training load in a professional soccer team throughout a full competitive season. Total distance, high-speed running distance (HSRD, > 18 km·h-1), highmetabolic load distance (HMLD, > 25.5 W·kg-1), player load and total number of impacts (above 3 G) were collected from training and match sessions in professional soccer players (n = 25) competing in LaLiga123. Comparisons of external load parameters by each match-related contextual variable were examined using a mixed-effect model. Differences between playing positions were found for total distance (p < 0.05; r = 0.11–0.15), HSRD (p < 0.05; r = 0.13–0.19), HMLD (p < 0.05; r = 0.12–0.19), player load (p < 0.05; r = 0.11–0.19) and impacts (p 0.05). In addition, a significant impact of match outcome (p < 0.05; r = 0.11–0.15), opponent level (p < 0.05; r = 0.11–0.17) and match location (p < 0.05; r = 0.14–0.20) on the weekly training load (before and after the match) was observed. In conclusion, match-related contextual variables seem to slightly affect weekly external training load. Thus, coaching and medical departments could consider the influence of these contextual variables when prescribing the training load relative to the match demands.